High-power impulse magnetron sputter deposition of TiBx thin films: Effects of pressure and growth temperature. (November 2019) - Hellgren, Niklas; Thörnberg, Jimmy; Zhirkov, Igor; Sortica, Maurico A.; Petrov, Ivan; Greene, J.E.; Hultman, Lars; Rosen, Johanna
Abstract: Titanium boride, TiBx, thin films are grown in pure Ar discharges by high-power impulse magnetron sputtering (HiPIMS) from a compound TiB2 target. Film compositions are determined by time-of-flight elastic recoil detection analysis and Rutherford backscattering spectrometry as a function of deposition temperature ( T s = 25–900 °C) and Ar pressure ( p A r  = 0.67–2.67 Pa, 5–20 mTorr). For reference, films are also grown by direct current magnetron sputtering (dcMS) under similar conditions. The HiPIMS waveform, average target power P T, and resulting film compositions are strongly dependent not only on p A r, but also on T s . At high pressures the effect of varying T s on P T is minimal, while at lower p A r the effect of T s is more pronounced, due to substrate-temperature-induced gas rarefaction. Films grown by HiPIMS at 0.67 Pa are understoichiometric, with B/Ti = 1.4–1.5, while at 2.67 Pa, B/Ti decreases from 2.4 to 1.4 as T s increases from 25 to 900 °C. dcMS-deposited films are overstoichiometric (B/Ti ≃ 3) when grown at low pressures, and near-stoichiometric (B/Ti ≃ 1.9–2.2) for higher p A r . All experimental results are explained by differences in the ionization potentials of sputtered Ti and B atoms, together with p A r - and T s -dependent gas-phase scattering. Highlights: Substrate heating-induced gas rarefaction affects HiPIMS discharge characteristics. Substrate heating-induced gas rarefaction reduces gas-phase scattering. Ionization potentials and gas-phase scattering control B/Ti ratios in TiBx films. HiPIMS-grown TiBx films are more sensitive to gas rarefaction than dcMS films.